Type 1 Tyrosinemia in an infant - Pablo Antonio Hernández Dinza; Carlos Ascanio Rodríguez; Odelinda Acosta Camacho (Centro Provincial de Información de Ciencias Médicas, 2018)
The case report of a 2 months of age patient is described who was born at term and normal in weight; she fed with exclusive breast feeding and she had a history of 2 previous admissions (severe anemia and common cold). She was hospitalized in the Intensive Therapy Service of "Dr. Antonio María Béguez Caesar" Southern Pediatric   Hospital  due to widespread edemas and ascites, with a fast clinical course to an acute liver failure. The metabolic tests of urine and blood allowed to confirm the diagnosis of type 1 tyrosinemia. In spite of offering her the required care, the patient had an unfavourable clinical course.